2008
DOI: 10.1007/s10661-008-0533-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of malodor pollutants and aromatic VOCs around an urban valley in Korea

Abstract: In this study, the environmental behavior of malodor pollutants (MPs) [including reduced sulfur compounds (RSCs)] and aromatic volatile organic compounds (AVOCs) were investigated around urban valley areas during several field campaigns (February through December 2006). The MPs measured in the study area include the RSCs (H(2)S, CH(3)SH, DMS, and DMDS), ammonia (NH(3)), and styrene (STY); the AVOCs include benzene (BEN), toluene (TOL), ethylbenzene (EB), m,p-xylene (MPX), and o-xylene (OX). The variation of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Results showed that OI for DMS throughout all study had a mean value of 1.82, minimum of 1.54 and maximum of 2.14. The odor intensity computed for the DMS is in good accordance with previous studies outside Singapore made either in ambient air at industrial sites [309,324,332,333] or in urban background air. [294,334,335]…”
Section: Derivation Of Odor Intensity (Oi)supporting
confidence: 86%
“…Results showed that OI for DMS throughout all study had a mean value of 1.82, minimum of 1.54 and maximum of 2.14. The odor intensity computed for the DMS is in good accordance with previous studies outside Singapore made either in ambient air at industrial sites [309,324,332,333] or in urban background air. [294,334,335]…”
Section: Derivation Of Odor Intensity (Oi)supporting
confidence: 86%
“…1). This city includes complex terrain with a valley area surrounded by a number of mountains, public buildings, and residential areas (Song et al 2009;Song et al 2010a). It also includes a variety of source regions (e.g., industrial complexes) of pollutant gases in the vicinity of the central downtown area (Fig.…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…1). Since the early 2000s, Yangsan city has rapidly become urbanized and industrialized, causing a substantial increase in the concentration of odorous pollutants due to large point sources, geographical features (e.g., semi-closed topography), and meteorological conditions (e.g., dispersion) (Song et al 2009b). It also includes a variety of source regions such as the industrial complexes (ICs) of Eogok (EG IC), Sanmak (SM IC), Yangsan (YS IC), and Bukjeong IC (BJ IC) located around an urban center area of Yangsan; Ungsang (US IC) and Ungbi IC (UB IC) located in the Ungsang area (the northeastern part of the study area) (Fig.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Air samples for the RSCs in eight sampling locations (S1 -S8), which are industrial source regions, were collected using a vacuum sampling system to fill a polyester aluminum bag (PAB) on 21 October 2008. The concentrations of RSCs were determined using a GC (GC-17A, Shimadzu Corp., Japan) with a flame photometric detector (FPD) (Song et al 2009b). The eight sampling locations were: S1 -S3, in tire plants (0.5 km away from EG IC); S4, in a waste water disposal plant (nearly 4 km south of EG IC); S5, in a oil refinery (located between SM and BJ ICs); S6, in a paper mill/incineration plant (a circumferential area of US IC); and S7 -S8, in livestock feedlots (located between US and UB ICs) (Fig.…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 1 more Smart Citation